1999
DOI: 10.1063/1.477982
|View full text |Cite
|
Sign up to set email alerts
|

Wall slip in the molecular dynamics simulation of thin films of hexadecane

Abstract: A molecular dynamics simulation of a thin liquid film as it is sheared between two planar walls is reported. The model liquid is composed of linear chain molecules of hexadecane (C16H34) with intramolecular architecture such as bond stretching, angle bending and dihedral potentials included in the model. Designing a model that can mimic the planar shear flow enables us to study important questions on the effects of the wall properties on the slip between the liquid film and the wall. Different properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
111
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 23 publications
11
111
1
1
Order By: Relevance
“…These simulations have shown that the slip length generally increases with increasing sliding velocity and pressure [168][169][170][171]. At very high sliding velocity, the slip length asymptotes towards a constant value [57].…”
Section: Boundary Slipmentioning
confidence: 85%
See 2 more Smart Citations
“…These simulations have shown that the slip length generally increases with increasing sliding velocity and pressure [168][169][170][171]. At very high sliding velocity, the slip length asymptotes towards a constant value [57].…”
Section: Boundary Slipmentioning
confidence: 85%
“…This can lead to large reductions in friction compared to the Couette case [146]. Slip has been commonly observed in NEMD simulations of thin fluid films confined between atomically-smooth surfaces [57,[168][169][170][171]. Many of these studies have quantified the slip length, which is defined as an extrapolated distance into the wall where the tangential velocity component vanishes (see Fig.…”
Section: Boundary Slipmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary slip is dependent on various factors, such as the wettability of the solid surface [32] , surface roughness [33] , the nanoscale vapor bubbles generated at the liquid-solid interface [34] , shear rate [35] , the electric double layer [36] , the shape and the arrangement of the liquid molecules [37] , variation of viscosity near the solid walls [38] , as summarized in Fig.1. For the slip of the confined liquid, Jabbarzadeh et al used a united atoms model in MD simulations to study the influence of wall properties on the slip between hexadecane film and the walls [39,40] . Pit et al probed the velocity of hexadecane within 80 nm from the solid wall and gave the direct experimental evidence of slip [41] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an excessive penetration of the wall atoms into the fluid phase reduces the slip velocity for soft thermal walls [21]. Nevertheless, the effect of thermal surface roughness on the slip length in the shear-rate-dependent regime was not systematically explored even for atomically smooth walls.…”
Section: Introductionmentioning
confidence: 99%